Corporate Governance and Bank Performance: Evidence from Employee Perspectives in Nepalese Development Banks (Quest Journal of Management and Social Sciences, 2025)
Background: Corporate governance ensures accountability, Transparency, and effective management in organizations, playing a crucial role in the stability and performance of banks. In Nepal, weak governance has historically contributed to banking crises, highlighting the need for stronger governance frameworks.Purpose: This study examines how corporate governance practices influence both financial and non-financial performance in Nepalese development banks, with a focus on employee perspectives. It aims to identify gaps and provide insights to enhance the effectiveness of governance and foster stakeholder trust.Design/methodology/approach: The study adopts an explanatory research design supported by Structural Equation Modeling (SEM). Primary data were collected from 407 employees across various development banks using a random sampling approach, out of which 384 responses were retained for final analysis. A structured survey instrument based on a five-point Likert scale was administered through the KOBO Toolbox. The data collected were processed using descriptive and inferential statistical techniques in MS Excel and Smart PLS 4.0 to assess trends, relationships, and the strength of governance influences.Findings: The results indicate that the Board of Directors, Audit Committee, and Transparency and Disclosure exert significant positive effects on non-financial performance, which in turn enhances financial performance. Conversely, CEO Duality shows no significant impact, highlighting that concentrated leadership roles do not necessarily contribute to better organizational outcomes. These findings reinforce the importance of robust governance mechanisms in driving organizational effectiveness.Conclusion: The study concludes that effective governance, particularly through active boards, strong audit committees, and transparent practice, is vital for enhancing both financial and non-financial performance in Nepalese development banks. The results offer practical implications for policymakers and bank management, emphasizing the need to strengthen oversight, promote ethical leadership, and reinforce Transparency to improve organizational stability and performance.Keywords: Corporate governance, bank performance, regulatory compliance, personnel management